Uplifting Emotional Scripts: Passions, Education, and Restoration in Valentinianism - Iricinschi, Eduard (Studi e materiali di storia delle religioni, 2020)
This paper investigates scenarios of emotional restoration in two sets of late antique writings, produced in the second century CE and circulated until early fifth century CE in Egypt: a Christian heresiological tome, Irenaeus of Lyon's Against Heresies; and four texts from the Coptic Nag Hammadi collection of texts, the Gospel of Truth, the Apocryphon of John, On the Origin of the World, and the Exegesis on the Soul. From the perspective advanced by this article, what unites all of the above lies at the intersection of history of religion and history of emotions. The paper explores various emotional landscapes shaped by error, ignorance, and fog in the Gospel of Truth, the affective tribulations of Sophia in Christian Valentinian texts, to unravel the upward trajectory of religiously articulated emotional scripts. In doing this, the article identifies the creation of a Platonic vocabulary of emotions in late-antique Egypt by following the metamorphosis of what could be informally termed as restorative affects in some religious texts circulating in fourth-century Egypt.